Sleep and Breathing International Journal of the Science and Practice of Sleep Medicine - Eliasson, Arn H.; Penzel, Thomas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Description The journal Sleep and Breathing aims to reflect the state of the art in the international science and practice of sleep medicine. The journal is based on the recognition that management of sleep disorders requires a multi-disciplinary approach and diverse perspectives. The initial focus of Sleep and Breathing is on timely and original studies that collect, intervene, or otherwise inform all clinicians and scientists in medicine, dentistry and oral surgery, otolaryngology, and epidemiology on the management of the upper airway during sleep. Furthermore, Sleep and Breathing endeavors to bring readers cutting edge information about all evolving aspects of common sleep disorders or disruptions, such as insomnia and shift work. The journal includes not only patient studies, but also studies that emphasize the principles of physiology and pathophysiology or illustrate potentially novel approaches to diagnosis and treatment. In addition, the journal features articles that describe patient-oriented and cost-benefit health outcomes research. Thus, with peer review by an international Editorial Board and prompt English-language publication, Sleep and Breathing provides rapid dissemination of clinical and clinically related scientific information. But it also does more: it is dedicated to making the most important developments in sleep disordered breathing easily accessible to clinicians who are treating sleep apnea by presenting well-chosen, well-written, and highly organized information that is useful for patient care. "Sleep and Breathing" is offering its authors free use of color and a rapid online publication.
Keywords: Dentistry; Internal medicine; Respiratory organs -- Diseases; Neurology; Otorhinolaryngology; Pediatrics; Pneumology/Respiratory System; Otorhinolaryngology; Dentistry; Neurology; Internal Medicine; Pediatrics